Civil war on Race Street : the civil rights movement in Cambridge, Maryland - Levy, Peter B. (Southern dissent., 2003)
''An important contribution to the historiography of the modern African-American freedom struggle. By focusing on a campaign located outside the Deep South (led principally by an African-American woman) that attracted an unprecedented level of federal investigation, Levy joins those scholars who are profitably extending our understanding of what the freedom struggle was, how it was organized, and even when and where it was to be found.